2016
DOI: 10.1186/s12936-016-1195-8
|View full text |Cite
|
Sign up to set email alerts
|

Frequent blood feeding enables insecticide-treated nets to reduce transmission by mosquitoes that bite predominately outdoors

Abstract: BackgroundThe effectiveness of vector control on malaria transmission by long-lasting insecticidal nets (LLINs) and indoor residual spraying (IRS) depends on the vectors entering houses to blood feed and rest when people are inside houses. In the Solomon Islands, significant reductions in malaria have been achieved in the past 20 years with insecticide-treated bed nets, IRS, improved diagnosis and treatment with artemisinin combination therapies; despite the preference of the primary vector, Anopheles farauti,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 35 publications
3
45
0
Order By: Relevance
“…These village "neighbourhoods" of parasite lineages appear to emanate from within-household co-transmission of highly related parasites. This radius of high genetic relatedness is consistent with the mosquito flight path (Charlwood, et al 1988;Russell, et al 2016). Thus, the fine scale patterns of population structure detected are likely to be driven by mosquito movement, rather than that of the human host.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These village "neighbourhoods" of parasite lineages appear to emanate from within-household co-transmission of highly related parasites. This radius of high genetic relatedness is consistent with the mosquito flight path (Charlwood, et al 1988;Russell, et al 2016). Thus, the fine scale patterns of population structure detected are likely to be driven by mosquito movement, rather than that of the human host.…”
Section: Discussionsupporting
confidence: 74%
“…Despite the principal vector in Solomon Islands, Anopheles farauti, feeding outdoors (Russell, et al 2016), much of the exposure to infective bites remains highly clustered around homes. This vector behaviour is considered to be a major challenge for elimination, but our data suggests that interventions focused on index households (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this study suggests four important findings for public health control: (1) API may be significantly lower at the provincial level compared to the sub-district level and varied accordingly, suggesting that malaria foci may be maintained in a locality from a provincial level, especially in areas of low to moderate endemicity; (2) the importance of mosquito abundance information may reflect malaria incidence rate in a location 42,43 ;…”
Section: Resultsmentioning
confidence: 79%
“…It has been shown that the distribution of ITNs is responsible for a reduction of 68% in malaria burden in sub-Saharan Africa 1 . This control method has been widely distributed and a dramatic increase in use has resulted in the mass utilization of ITNs in many countries 2,3 . Additionally, personal protection has been found to be effective against mosquito bites and its use has led to a reduction in malaria infection 4-6 .…”
Section: Introductionmentioning
confidence: 99%
“…It should, therefore, have been expected that endophilic malaria vectors, such as A. gambiae and A. funestus would gradually change their feeding and resting behaviour as a reaction against the current strategies of indoor spreading of insecticides and the distribution of ITNs. In fact, evidence of changes in biting and resting behaviour of malaria vectors, have been mounting up in recent years [ 9 13 ]. The presence of outdoor-activity, early-biting malaria vectors have been reported in many countries in Africa, such as Benin [ 14 ], Tanzania [ 15 ], Kenya [ 16 18 ], Nigeria [ 19 ], Uganda [ 20 ], Gambia [ 21 ], Ghana [ 22 ] and Rwanda [ 23 ], amongst others.…”
Section: Introductionmentioning
confidence: 99%